2016
DOI: 10.1159/000444206
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Management of Systemic Amyloidosis in Western Countries

Abstract: Background: Amyloidosis has been a mystery for centuries, but research of the last decennia has clarified many of the secrets of this group of diseases. A protein-based classification of amyloidosis helps to understand problems that were part of the obsolete clinical classification in primary, secondary, and familial amyloidosis. All types of amyloid are secondary to some underlying precursor-producing process: each type is caused by a misfolded soluble precursor protein that becomes deposited as insoluble amy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
93
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(100 citation statements)
references
References 53 publications
0
93
0
7
Order By: Relevance
“…1,4,5,7,15,19 For example, in a study by Weiss et al, 59% of the 1,430 AL amyloidosis patients identified in Sweden between 1995 and 2013 were men. 4 In another Swedish study by Hemminiki et al with 813 AL amyloidosis patients identified between 2001 and 2008, men were found to have a 1.3 times higher incidence of the disease than women.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,4,5,7,15,19 For example, in a study by Weiss et al, 59% of the 1,430 AL amyloidosis patients identified in Sweden between 1995 and 2013 were men. 4 In another Swedish study by Hemminiki et al with 813 AL amyloidosis patients identified between 2001 and 2008, men were found to have a 1.3 times higher incidence of the disease than women.…”
Section: Discussionmentioning
confidence: 99%
“…Awareness is essential for timely detection and treatment of amyloidosis. 19 We further call for widespread education about the disease, as many institutions lack the training and resources to support these educational efforts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amyloidosis is one of the most serious potential complications of FMF, which is characterized by extracellular deposition of pathological insoluble fibrillar proteins in organs and tissues that is localized or systemic . Amyloid deposition detected in the gingiva is called ligneous periodontitis (LP) which is also an inflammatory destructive membranous disease characterized by a plasminogen (PLG) deficiency …”
Section: Introductionmentioning
confidence: 99%
“…These diseases are characterized by the formation of abnormal protein filaments, termed amyloid fibrils, which deposit inside the tissue (Chiti & Dobson, 2017). Examples hereof are Alzheimer's or Parkinson's diseases (Chiti & Dobson, 2017) or the various forms of systemic amyloidosis (Nienhuis et al, 2016). Examples hereof are Alzheimer's or Parkinson's diseases (Chiti & Dobson, 2017) or the various forms of systemic amyloidosis (Nienhuis et al, 2016).…”
Section: Introductionmentioning
confidence: 99%